SEMEN CHARACTERISTICS AS INFLUENCED BY SEASONAL AND CLIMATIC VARIATIONS IN NILI-RAVI BUFFALO BREEDING BULLS - S. Hameed; S. Masood; H. Zaneb; M. S. Khan; M. Younis; Habib-ur-Rehman; M. Avais; M. U. R. Khan (Journal of Animal and Plant Sciences, 2017)
The present study was conducted to determine the effect of seasonal and climatic variations on semen characteristics of Nili-Ravi buffalo breeding bulls in Sahiwal and Bahawalpur districts of Punjab, Pakistan. For this purpose, 14 adult Nili-Ravi buffalo breeding bulls (n=7 from each of Semen Production Unit (SPU) Qadirabad, Sahiwal and SPU Karaniwala, Bahawalpur), were used. Semen samples were collected fortnightly using artificial vagina. On each collection day, 2 ejaculates were collected from each bull. Results demonstrated significantly higher (P<0.05) ejaculatory volume in buffalo bulls of Sahiwal compared to Bahawalpur district, whereas seasonal influence on ejaculatory volume was non-significant (P>0.05). Semen color score was non-significantly different (P>0.05) between the districts with higher score in Sahiwal and it was higher in autumn and spring seasons but with non-significant (P>0.05) seasonal influence. Semen pH was significantly lower (P<0.05) in Sahiwal than Bahawalpur and significantly lower (P<0.05) pH was observed in autumn season. Mass motility score was non-significantly different (P>0.05) between the districts with higher score in Sahiwal and it was higher in autumn season but with non-significant influence of seasons. Significantly higher (P<0.05) individual sperm motility in Sahiwal was recorded as compared to Bahawalpur and it was higher in spring and autumn in Sahiwal. Sperm concentration was significantly increased (P<0.05) in Sahiwal than Bahawalpur. Similarly season influence was also significant with significantly higher (P<0.05) sperm concentration in autumn and spring. In conclusion, semen quality of Nili-Ravi buffalo breeding bulls is superior in autumn and spring and the bulls in Sahiwal district produce superior quality semen compared to Bahawalpur district.
Keywords: Nili-Ravi; Buffalo; Bull; Semen; Season; Climate